Outcome of Laser Urethrotomy in Comparison with Optical Internal Urethrotomy in Recurrent Stricture Urethra Following Perineal Anastomotic Urethroplasty for PUDD (Bangladesh Journal of Urology, 2020)
Objective: To compare the outcome of laser urethrotomy and optical internal urethrotomy(OIU) for the treatment of recurrent stricture urethra following perineal anastomotic urethroplasty for posterior urethral distraction defect.Materials and methods: The study was conducted in Dhaka Medical College Hospital from January 2013 to December 2014.Male patients presented with obstructed voiding symptoms following perineal anastomotic urethroplasty were evaluated by their history, physical findings and investigations (urinalysis, uroflowmetry, retrograde urethrogram and micturiting cystourethrogram ) & primarily 64 patients are selected by purposive sampling. Patients are divieded again by random allocation into group A and group B and underwent for OIU and laser urethrotomy respectively.Results: Comparison was made to find out the better method between optical urethrotomy and laser urethrotomy. Overall per-operative complications (bleeding, extravasations of irrigating fluid, false passage and broken knife) in the former group were 31.3% compared to none in the latter group. Post-operative complications like bleeding, haematoma, penile oedema and erectile dysfunction were found only in Group-A (p=0.002). The mean duration of postoperative catheterization and average hospital stay were observed to be much higher in Group-A than that in Group-B (p=0.000008; p=0.0006). Comparison of final outcome (development of stricture) between groups at 1 year of evaluation in Group-A and Group-B was not significant (p= 0.320).Conclusion: Laser urethrotomy is better than optical urethrotmy in regards of peroperative and post-operative complications.Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.181-187